[Rezension von: Riordan, Patrick, 1950-, Human dignity and liberal politics : Catholic possibilities for the common good] - Brady, Bernard V. (A journal of church and state, 2025)
Patrick Riordan’s book defends and dissects contemporary Catholic teachings on the common good, which promotes conditions for human flourishing. Those cond